2015
DOI: 10.1186/s12889-016-2717-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure in adolescent girls: correlation to body size and composition

Abstract: BackgroundTo improve understanding of the pathophysiology of hypertension in adolescents and pave the way for risk stratification, studies have sought to determine the correlates of blood pressure (BP). Inconsistencies in dependent and independent variables have resulted in an elusive consensus. The aim of this report is to examine an inclusive array of correlates of BP, as a continuous (systolic and diastolic BP) and a dichotomous variable.MethodsSubjects were a school-based sample of 730 urban, mostly Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
3
7
0
1
Order By: Relevance
“…The relation between obesity and blood pressure is consistent with the previous researches (23)(24)(25)(26)(27)(28). Farah and the collaborators (29) have made systematic review of randomized clinical trials in which the physical training effects of blood pressure in obese adolescents were researched.…”
Section: Discussionsupporting
confidence: 80%
“…The relation between obesity and blood pressure is consistent with the previous researches (23)(24)(25)(26)(27)(28). Farah and the collaborators (29) have made systematic review of randomized clinical trials in which the physical training effects of blood pressure in obese adolescents were researched.…”
Section: Discussionsupporting
confidence: 80%
“…We discovered that puberty onset increased SBP and DBP in boys and girls, but after adjusting for covariates, the relationship between pubertal development and BP levels and EBP was stronger in girls than boys. Some studies pointed out that the effect of pubertal development on BP appeared to operate through body fat 12,28 . Prior studies showed that adolescent girls gained more body fat than boys 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 27 Another study also found puberty stage was correlated to SBP and DBP, but it was not included in the regression model. 28 Several researches speculated that the effect of sexual maturation on BP appeared to operate through age, height, and body size. 11 , 12 In this study, we investigated the differences in BP levels between puberty group and prepuberty group by age group, and controlled the effects of age, and BMI in regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies show that puberty, especially when it starts early, may be related to higher BP levels, and that girls appear to have a greater increase in BP levels during puberty than boys [35,36]. This seems to be related mainly to body composition and to the fact that girls gain more fat mass than boys [37]. Also, very short or tall children may have their BP misclassified when using only the NIH/NHLBI BP tables [38].…”
Section: Discussionmentioning
confidence: 99%